Open syllable lengthening in Middle Dutch: Evidence from verse - Sytsema, J; Lahiri, A (Cambridge University Press, 2018)
This paper attempts to determine a more precise timeline for the onset of Open Syllable Lengthening in Dutch. We examined two late 14th-century Brabantic texts in the Manuscript Marshall 29 (1375 AD), Mellibeus and Saladijn, and compared these with an older Brabantic text Lutgart to ascertain when exactly Open Syllable Lengthening originated in (Brabantic) Middle Dutch. A combination of diachronic correspondences and a careful examination of the texts written in verse during the course of approximately 75 years has helped us to establish the synchronic systems of 13th- and 14th-century Middle Dutch, and, furthermore, has allowed us to determine the onset of prosodic changes such as Open Syllable Lengthening. Orthographic, rhythmic, and metrical evidence from the three texts suggests that the process was incomplete in the earliest period and was finalized in the late 14th century in Brabant, thereby refuting the standard assumption that the lengthening was completed before the onset of Middle Dutch in general.